IMPACT OF POVERTY, STUNTING AND WASTING ON THE SPECIFIC INDEX FOR STUNTING MANAGEMENT IN TODDLERS AGED 0-59 MONTHS IN DOMPU - Mantikaisih Laras, Andi Tenri; Kosasih; Malik, Rahadian (PG PAUD Universitas Negeri Surabaya, 2024)
This research aims to obtain an analysis regarding the influence of poverty, stunting, and wasting on the special index for stunting management in children aged 0-59 months in Dompu Regency, West Nusa Tenggara, both partially and simultaneously. This research uses a descriptive quantitative approach, with the population being all toddlers aged 0-59 months in 10 health center areas in Dompu Regency, covering a period of 7 years from 2017 to 2023. The techniques used to collect data are literature study and documentation study, as this research utilizes secondary data. The data processing method in this research employs SPSS version 25. The research results indicate that poverty, stunting, and wasting have a positive and significant simultaneous effect on the special index for stunting management. However, when examined individually, poverty and stunting do not have a significant effect on the special index for stunting management, while wasting does have a positive and significant effect on it. Referring to the results of this research, efforts to maintain and even improve the variables that are still considered lacking in this study are necessary so that the rates of poverty, stunting, and wasting continue to decline, and the index specifically for stunting management increases as a form of the government's successful performance. Keywords: Poverty, Stunting, Wasting, Nutrition Status, Special Index of Stunting